Adverse Maternal and Neonatal Outcomes in Indicated Compared with Spontaneous Preterm Birth in Healthy Nulliparas: A Secondary Analysis of a Randomized Trial - Tita, Alan T.; Doherty, Lindsay; Roberts, Jim M.; Myatt, Leslie; Leveno, Kenneth J.; Varner, Michael W.; Wapner, Ronald J.; Thorp, John M., Jr; Mercer, Brian M.; Peaceman, Alan; Ramin, Susan M.; Carpenter, Marshall W.; Iams, Jay; Sciscione, Anthony; Harper, Margaret; Tolosa, Jorge E.; Saade, George R.; Sorokin, Yoram; for the National Institute of Child Health and Human Development Maternal-Fetal Medicine Units Network (American Journal of Perinatology, 2018)
Objective To compare the risks of adverse maternal and neonatal outcomes associated with spontaneous (SPTB) versus indicated preterm births (IPTB).Methods A secondary analysis of a multicenter trial of vitamin C and E supplementation in healthy low-risk nulliparous women. Outcomes were compared between women with SPTB (due to spontaneous membrane rupture or labor) and those with IPTB (due to medical or obstetric complications). A primary maternal composite outcome included: death, pulmonary edema, blood transfusion, adult respiratory distress syndrome (RDS), cerebrovascular accident, acute tubular necrosis, disseminated intravascular coagulopathy, or liver rupture. A neonatal composite outcome included: neonatal death, RDS, grades III or IV intraventricular hemorrhage (IVH), sepsis, necrotizing enterocolitis (NEC), or retinopathy of prematurity.Results Of 9,867 women, 10.4% (N = 1,038) were PTBs; 32.7% (n = 340) IPTBs and 67.3% (n = 698) SPTBs. Compared with SPTB, the composite maternal outcome was more frequent in IPTB—4.4% versus 0.9% (adjusted odds ratio [aOR], 4.0; 95% confidence interval [CI], 1.4–11.8), as were blood transfusion and prolonged hospital stay (3.2 and 3.7 times, respectively). The frequency of composite neonatal outcome was higher in IPTBs (aOR, 1.8; 95% CI, 1.1–3.0), as were RDS (1.7 times), small for gestational age (SGA) < 5th percentile (7.9 times), and neonatal intensive care unit (NICU) admission (1.8 times).Conclusion Adverse maternal and neonatal outcomes were significantly more likely with IPTB than with SPTB.
Keywords: spontaneous preterm birth; indicated preterm birth; preeclampsia; pregnancy outcomes